Comparative visual performance with monofocal and multifocal intraocular lenses - Gundersen, Kjell Gunnar (Dove Medical Press, 2013)
BACKGROUND: To compare near, intermediate, and distance vision, and quality of vision using appropriate subjective questionnaires, when monofocal or apodized diffractive multifocal intraocular lenses (IOLs) are binocularly implanted. METHODS: Patients with different binocular IOLs implanted were recruited after surgery and had their visual acuity tested, and quality of vision evaluated, at a single diagnostic visit between 3 and 8 months after second-eye surgery. Lenses tested included an aspheric monofocal and two apodized diffractive multifocal IOLs with slightly different design parameters. A total of 94 patients were evaluated. RESULTS: Subjects with the ReSTOR® +2.5 D IOL had better near and intermediate vision than those subjects with a monofocal IOL. Intermediate vision was similar to, and near vision slightly lower than, that of subjects with a ReSTOR® +3.0 D IOL implanted. The preferred reading distance was slightly farther out for the +2.5 D relative to the +3.0 D lens, and farthest for the monofocal. Visual acuity at the preferred reading distance was equal with the two multifocal IOLs and significantly worse with the monofocal IOL. Quality of vision measures were highest with the monofocal IOL and similar between the two multifocal IOLs. CONCLUSION: The data indicate that the ReSTOR +2.5 D IOL provided good intermediate and functional near vision for patients who did not want to accept a higher potential for visual disturbances associated with the ReSTOR +3.0 D IOL, but wanted more near vision than a monofocal IOL generally provides. Quality of vision was not significantly different between the multifocal IOLs, but patient self-selection for each lens type may have been a factor.